ON CONCEPTUAL APPROACHES TO DIGITAL TRANSFORMATION OF THE NATIONAL ECONOMY OF BELARUS - D. M. Krupsky (Цифровая трансформация, 2018)
The article contains the author's presentation of the concept of "digital transformation of the national economy". Various aspects of the digital transformation of the economy are considered. The analysis of key conditions and prerequisites for successful digital transformation of the national economy of the Republic of Belarus is presented. The issues of digitalization of the industrial complex are considered. A set of principles for the digital transformation of the Belarusian economy, which is exhaustive from the point of view of sufficiency for determining the strategy and the organizational and economic mechanism for the implementation of digital transformation, is proposed. The key directions of the digital transformation of the Belarusian economy, covering the development of the corresponding infrastructure, as well as digitalization of the sphere of services and material production, are determined. Different approaches to the organization of digital transformation of the national economy of the Republic of Belarus are proposed, and the issues of determining the authorized state body responsible for its implementation are considered. The advantages and disadvantages of each of the presented approaches are analyzed. Based on the world experience, an algorithm for organizing the digital transformation of the Belarusian economy has been formed, taking into account the existing institutional environment.